Increased hepatic acylcarnitines after oral administration of amiodarone in rats. Issue 7 (21st February 2020) - Kim, Gabin; Choi, Hyung‐Kyoon; Lee, Hwanhui; Moon, Kyoung‐Sik; Oh, Jung Hwa; Lee, Jaeick; Shin, Jae Gook; Kim, Dong Hyun
Abstract: Amiodarone is known to induce hepatic injury in some recipients. We applied an untargeted metabolomics approach to identify endogenous metabolites with potential as biomarkers for amiodarone‐induced liver injury. Oral amiodarone administration for 1 week in rats resulted in significant elevation of acylcarnitines and phospholipids in the liver. Hepatic short‐ and medium‐chain acylcarnitines were dramatically increased in a dose‐dependent manner, while the serum levels of these acylcarnitines did not change substantially. In addition, glucose levels were significantly increased in both the serum and liver. Gene expression profiling showed that the hepatic mRNA levels of Cpt1, Cpt2, and Acat1 were significantly suppressed, whereas those of Acot1, Acly, Acss2, and Acsl3 were increased. These results suggest that hepatic acylcarnitines and glucose levels might be increased due to disruption of mitochondrial function and suppression of glucose metabolism. Perturbation of energy metabolism might be associated with amiodarone‐induced hepatotoxicity. Abstract : Increases in hepatic short‐, medium‐ and long chain acylcarnitines and glucose levels were observed in rats after oral treatment of amiodarone. Also, hepatic mRNA levels of Cpt1, Cpt2, and Acat1 were significantly suppressed whereas those of Acot1, Acly, Acss2 and Acsl3 were increased. These results might be due to the perturbation of mitochondrial function, leading to amiodarone‐induced hepatotoxicity.